Susceptibility of corythaica cyathicollis costa to a native isolation of beauveria bassiana (vuillemin) (2012)
The research aimed to evaluate a native isolation of B. bassiana under laboratory conditions as a biological alternative control for the eggplant lace bug (C. cyathicollis). The experiments were conducted in the Pathology and Entomology Laboratories at the Universidad de Córdoba, Monteria (Colombia). Initially, the pathogenicity of B. bassiana on adult insects was studied using a concentration of 1·107 spores/mL, in which mortality and intrinsic mortality were determined, in addition, the presented symptomatology was described. Subsequently, the concentrations 1·100 (control treatment), 1·103, 1·105, 1·106, 1·107 and 1·108 spores/mL were evaluated to determine the lethal concentrations of CL50 and CL90 through Probit analysis. The results obtained showed that the native isolation was pathogenic since post-inoculation was observed, between the fifth and sixth days, with 50% mortality (and 87.7% at 12 days), in addition, the intrinsic mortality was 92.4%. The symptomatology showed loss of mobility and lack of appetite between 11 and 12 hours post-inoculation, approximately, and the presence of mycelium 2 days after death. The percentages of mortality for the evaluated concentrations were 0, 46.6, 73.3, 83.3, 90.0 and 96.6% respectively, and the lethal concentrations of CL50 and CL90 were 1.8·103 and 6.5·106 spores/mL respectively. These results indicate the potential of entomopathogenic fungus as an alternative that could be articulated into integrated pest management.